Preparation method and application of molybdenite / ZnO nanorod with pillared structure
By forming a column-supported structure in commercially available molybdenum ore and combining zinc oxide nanorods, the problem of low-temperature NO2 detection is solved, and high sensitivity and low-cost NO2 monitoring is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411311785.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The prior art is difficult to effectively monitor ppb-level NO2 at low temperatures, and the preparation method of sensing materials is high energy consumption, complex equipment and low yield, resulting in insufficient gas permeability and insufficient surfactant sites.
The preparation method of the column-supported molybdenite/ZnO nanorod is adopted. By adding zinc acetate methanol solution and sodium hydroxide solution to the commercially available molybdenite, a heterogeneous column-supported structure is formed, and the zinc oxide nanorod is combined to improve the material. Surface area and active sites enable room temperature NO2 detection.
It realizes high sensitivity detection of ppb-level NO2 at room temperature, reduces preparation cost and energy consumption, improves the stability and sensitivity of materials, and is suitable for industrial production.
Smart Images

Figure CN119191352A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas sensing technology, and more particularly to a method for preparing pillared molybdenite / ZnO nanorods and an application thereof in NO2 monitoring. Background Art
[0002] Nitrogen dioxide (NO2) is one of the most toxic air pollutants, and its main sources are the burning of fossil fuels and industrial production. In addition to forming acid rain, photochemical smog and destroying the ozone layer, it also has a significant impact on human health. For example, respiratory diseases: irritation of the respiratory tract, triggering or aggravating diseases such as asthma and bronchitis, and increasing the risk of cardiovascular disease. Immune system damage: reduced immune function and increased risk of infection. Nitrogen dioxide (NO2) is seriously harmful even at the ppb level. The U.S. Environmental Protection Agency sets the NO2 standard for air quality control at 53ppb. Continuous or frequent exposure to NO2 concentrations above the air quality standard of 53ppb may lead to an increase in the incidence of acute respiratory and olfactory paralysis. Therefore, it is of great significance to achieve convenient and timely monitoring of trace NO2.
[0003] The detection of nitrogen dioxide (NO2) is through the adsorption and activation of the adsorption sites and active sites on the sensitive material. After activation, the charge of the sensitive material is transferred, causing the resistivity of the sensitive material to change. However, the materials commonly used for nitrogen dioxide (NO2) detection are mainly based on metal oxide semiconductors, which are widely studied due to their simple preparation methods and low costs. In particular, ZnO has become one of the most promising NO2 sensing materials due to its high sensitivity and high selectivity to NO2. However, metal oxides usually require higher operating temperatures (150-400℃), which limits their application at low temperatures. UV activation is considered to be an effective strategy for achieving NO2 sensing through various semiconductor nanostructures at room temperature, but this strategy still requires relatively harsh ultraviolet light irradiation.
[0004] Studies have found that MoS2 is the main component of molybdenite, which has the advantages of high specific surface area, rich active sites, excellent electrical properties and easy integration with other materials. Recently, it has been widely used in the fields of lubricants, catalysts, photocatalysts, electronic devices, energy storage devices and gas sensors. MoS2 has high sensitivity, good selectivity and low operating temperature for NO2 detection, and MoS2 has a multilayer structure, which is conducive to the adsorption and transmission of NO2. However, the current preparation methods of MoS2 are mainly mechanical exfoliation, liquid phase exfoliation, hydrothermal / solvothermal method, etc. These preparation methods require high energy consumption, complex equipment and low yield of MoS2. The present invention directly uses commercially available molybdenite as raw material to prepare gas-sensitive materials, reducing the cost of material preparation. However, the stacking and aggregation of molybdenite (MoS2) leads to insufficient gas permeability and insufficient surface active sites involved in the sensing process. Therefore, the construction of pillared structures is considered to be a promising strategy to solve the problems of stacking and agglomeration of two-dimensional materials, which can be achieved by inserting and growing specific nanostructures between layers. The pillared structure has the advantages of a larger surface area, increases the exposure of active sites and enhances the transfer of charge carriers.
[0005] Therefore, providing a pillared molybdenite / ZnO gas sensing material that can respond to ppb-level NO2 and a preparation method thereof is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0006] In view of this, the present invention provides a preparation method of pillared molybdenite / ZnO nanorods and its application. The preparation process of the method is simple, and the preparation process does not involve the use of high-end instruments and equipment, which is conducive to the industrial production of materials. A molybdenite / ZnO heterogeneous pillared structure material synthesized by the method responds to ppb-level NO2 under simulated sunlight at room temperature.
[0007] One of the purposes of the present invention is to provide a method for preparing pillared molybdenite / ZnO nanorods, comprising the following steps:
[0008] (1) Dispersing commercially available molybdenite into a zinc acetate methanol solution under stirring until adsorption equilibrium is reached to obtain a solution A for standby use;
[0009] (2) adding sodium hydroxide methanol solution to solution A, continuously stirring, centrifuging, washing and drying to obtain molybdenite / ZnO nanoparticles;
[0010] (3) dispersing the molybdenite / ZnO nanoparticles into deionized water and stirring evenly to obtain a molybdenite / ZnO nanoparticle suspension for later use;
[0011] (4) Under stirring, the molybdenite / ZnO nanoparticle suspension is added to the sodium hydroxide solution of ε-Zn(OH)2, stirred for 10 minutes, aged at elevated temperature, stirred again, washed, and dried overnight to obtain the molybdenite / ZnO nanorods with heterogeneous pillared structure.
[0012] Furthermore, the purity of MoS2 in the commercially available molybdenite is ≥99%.
[0013] Furthermore, in step (1), the solid-to-liquid ratio of the commercially available molybdenite to the zinc acetate methanol solution is 1 mg:1 mL; and the concentration of the zinc acetate methanol solution is 2.0 mol / L.
[0014] Furthermore, in step (2), the concentration of the sodium hydroxide methanol solution is 2.0-16.0 mol / L; the molar ratio of zinc ions to sodium ions in step (2) is 1:6.25-25; the stirring speed is 0-600 rpm, the centrifugal speed is 2000 rpm, and the drying is performed at 20-30° C. for 12-24 h.
[0015] The beneficial effect of adopting the above technical solution is that under this process, the zinc oxide nanoparticles form a better pillaring structure between the layers of molybdenite. The low speed centrifugation is to avoid destroying the pillaring structure.
[0016] Furthermore, in step (3), the solid-liquid ratio of the molybdenite / ZnO nanoparticles to deionized water is 10 mg:1 mL; and the stirring speed is 0-600 rpm.
[0017] Furthermore, in step (4), the preparation method of ε-Zn(OH)2 is: adding sodium hydroxide solution dropwise into zinc sulfate solution under stirring, reacting fully, washing and drying the precipitate to obtain ε-Zn(OH)2; the stirring speed is 0-600rpm; the aging temperature is 60-100°C, and the aging time is 0.5 hours.
[0018] Furthermore, the concentration of the sodium hydroxide solution is 2.0-4.0 mol / L, the concentration of the zinc sulfate solution is 1.0-2.0 mol / L, and the molar ratio of the sodium hydroxide to the zinc sulfate is 2:1; the stirring speed is 100-700 rpm, and the drying is carried out at 15-20° C. for 22-26 hours.
[0019] Furthermore, in step (4), the mass ratio of ε-Zn(OH)2 to molybdenite / ZnO nanoparticles is 3.48:0.1, the liquid-to-solid ratio of the sodium hydroxide solution to molybdenite / ZnO nanoparticles is 200mL:0.1g, and the concentration of the sodium hydroxide solution is 4.0mol / L; the stirring speed is 200-800rpm, and the stirring is repeated for 20-40min, and the drying condition is 60°C.
[0020] The beneficial effects of the above technical solution are as follows: under the process conditions, the pillared structure of molybdenite / ZnO nanorods prepared with ε-Zn(OH)2 as a precursor and molybdenite / ZnO nanoparticles as seeds is more stable, the sensing sensitivity is higher and the detection limit is lower, and the zinc oxide nanoparticles grown between the molybdenite sheets increase the electron transmission channels and adsorption sites and active sites, thereby improving the stability and sensitivity. The zinc oxide nanorods are formed on the surface of molybdenite / ZnO, which increases more adsorption sites and active sites, so that it has better sensing performance.
[0021] Further preferably, the purity of zinc acetate dihydrate used to prepare the zinc acetate methanol solution is ≥99%, and the purity of methanol is ≥99.5%; the purity of the sodium hydroxide is ≥99.5%, and the purity of the zinc sulfate is ≥99%.
[0022] The technical concept of the present invention is: MoS2 has a high specific surface area and abundant active sites. MoS2 has high sensitivity, good selectivity and low operating temperature for NO2 detection, and MoS2 has a multilayer structure, which is conducive to the adsorption and transmission of NO2. However, due to the stacking of the layer structure, the reduction of its active sites reduces the gas-sensitive performance, and the pillared structure can well solve the problem of MoS2 stacking. Zinc oxide nanorods have the characteristics of high specific surface area, excellent electronic properties, rich morphology and size controllability, good chemical stability and thermal stability, low cost and easy preparation, so the pillared MoS2 is combined with zinc oxide nanorods to prepare high-performance gas-sensitive materials.
[0023] The active sites of the molybdenite / ZnO nanorod composite material of the present invention are oxygen active sites. After NO2 is adsorbed by the composite material, it is oxidized by its oxygen active sites, resulting in a change in the resistivity of the material. The formation mechanism is that the molybdenite / ZnO nanoparticles and the zinc oxide nanorods form a heterogeneous structure, and changing the morphology of zinc oxide on the surface of the molybdenite / ZnO nanoparticles can also increase its specific surface area and active sites.
[0024] The second purpose of the present invention is to provide an application of pillared molybdenite / ZnO nanorods, which monitor 50 ppb NO2 under simulated sunlight conditions at room temperature.
[0025] Since molybdenite with a lamellar structure has good adsorption capacity and abundant active sites, NO2 is easily oxidized on the surface of the material, and the pillar structure improves the stability of the material and enhances its electron transmission ability and sensitivity. The growth of zinc oxide nanorods on the surface of molybdenite / ZnO nanoparticles increases the active sites and enhances the sensitivity and low-temperature activity of the material.
[0026] The key to the formation of pillared molybdenite / ZnO nanoparticles of the present invention is the stirring speed, the concentration of zinc acetate methanol solution, the concentration of sodium hydroxide methanol solution and the speed of dropping zinc acetate methanol solution. The formation of pillared molybdenite / ZnO nanorods is comprehensively determined by the stirring speed, the concentration of sodium hydroxide solution, the amount of molybdenite / ZnO seed crystals, the amount of ε-Zn(OH)2 precursor, the aging time and the aging temperature.
[0027] It can be seen from the above technical solution that, compared with the prior art, the beneficial effects of the present invention are:
[0028] (1) The gas-sensitive material of the present invention has the characteristics of simple preparation method and low cost. The molybdenite / ZnO nanorods prepared by the above method have good NO2 response performance.
[0029] (2) This method uses an adjustable molar ratio of zinc ions to sodium ions, which can adjust its adsorption and transmission capacity for NO2, while also regulating the number of active sites and electron transmission capacity, which is of great value in the field of room temperature NO2 sensing.
[0030] (3) The synthesis temperature of this method is relatively low. Except for the high aging temperature, the rest of the synthesis process is completed at room temperature, which is more environmentally friendly than other synthesis methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0032] Figure 1 This is the SEM image of the molybdenite / ZnO nanorods prepared in Example 3.
[0033] Figure 2 This is the response diagram of the molybdenite / ZnO nanorods prepared in Example 3 to 50 ppb NO2. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the embodiments of the present invention, the purity of MoS2 in molybdenite is ≥99%, the purity of zinc acetate dihydrate is ≥99%, the purity of methanol is ≥99.5%, the purity of sodium hydroxide is ≥99.5%, and the purity of zinc sulfate is ≥99%.
[0036] Example 1
[0037] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0038] (1) 100 mg of molybdenite was dispersed in 100 mL of a 2.0 mol / L methanol solution of zinc acetate dihydrate, stirred at room temperature for 1 h to reach adsorption equilibrium, 312.5 mL of a 4.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:6.25, stirred at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then with ethanol 2 times, and vacuum dried at 25 ° C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0039] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0040] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 mL of deionized water, added to 200 mL of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, heated to 80°C and aged for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0041] The molar ratio of zinc ions to sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 1 is 1:6.25. The material responds to a NO2 concentration of 50 ppb under simulated sunlight irradiation, and responds after NO2 is introduced into the gas chamber for 35 seconds. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 50% of the initial state, and the stability is general.
[0042] Example 2
[0043] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0044] (1) 100 mg of molybdenite was dispersed in 100 mL of a 2.0 mol / L methanol solution of zinc acetate dihydrate, stirred at room temperature for 1 h to reach adsorption equilibrium, and 312.5 mL of an 8.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:12.5. The mixture was stirred at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then washed with ethanol twice, and dried in vacuum at 25 °C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0045] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0046] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 mL of deionized water, added to 200 mL of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, heated to 80°C and aged for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0047] The molar ratio of zinc ions to sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 2 is 1:12.5. The material responds to a NO2 concentration of 50 ppb under simulated sunlight irradiation, and responds after NO2 is introduced into the gas chamber for 19 seconds. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 76% of the initial state, and the stability is general.
[0048] Example 3
[0049] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0050] (1) 100 mg of molybdenite was dispersed in 100 mL of a 2.0 mol / L methanol solution of zinc acetate dihydrate, stirred at room temperature for 1 h to reach adsorption equilibrium, and 625 mL of an 8.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:25. The mixture was stirred at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then washed with ethanol twice, and dried in vacuum at 25 °C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0051] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0052] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 ml of deionized water, added to 200 ml of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, heated to 80°C and aged for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0053] The molar ratio of zinc ion and sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 3 is 1:25. The material responds to NO2 concentration of 50 ppb and responds when NO2 is introduced into the gas chamber for 5s. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 95% of the initial state, and the stability is very good.
[0054] Example 4
[0055] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0056] (1) 100 mg of molybdenite was dispersed in 100 mL of a 2.0 mol / L methanol solution of zinc acetate dihydrate, stirred at room temperature for 1 h to reach adsorption equilibrium, and 312.5 mL of a 16.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:25. The mixture was stirred at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then washed with ethanol twice, and dried in vacuum at 25 °C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0057] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0058] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 mL of deionized water, added to 200 mL of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, heated to 80°C and aged for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0059] The molar ratio of zinc ion and sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 4 is 1:25. The material responds to a NO2 concentration of 50ppb under simulated sunlight irradiation, and responds when NO2 is introduced into the gas chamber for 30 seconds. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 60% of the initial state, and the stability is general.
[0060] Example 5
[0061] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0062] (1) 100 mg of MoS2 prepared by hydrothermal method was dispersed in 100 mL of 2.0 mol / L methanol solution of zinc acetate dihydrate, stirred at room temperature for 1 h to reach adsorption equilibrium, and 625 mL of 8.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:25. After stirring at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then washed with ethanol twice, and vacuum dried at 25 °C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0063] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0064] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 mL of deionized water, added to 200 mL of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, heated to 80°C and aged for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0065] The molar ratio of zinc ion and sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 5 is 1:25. The material responds to a NO2 concentration of 50ppb under simulated sunlight irradiation, and responds after NO2 is introduced into the gas chamber for 5s. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 96% of the initial state, and the stability is very good.
[0066] Example 6
[0067] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0068] (1) 100 mg of MoS2 molybdenite with a purity of 90% was dispersed in 100 mL of a 2.0 mol / L methanol solution of zinc acetate dihydrate, and stirred at room temperature for 1 h to reach adsorption equilibrium. 625 mL of a 8.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:25. The mixture was stirred at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then washed with ethanol twice, and vacuum dried at 25 ° C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0069] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0070] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 mL of deionized water, added to 200 mL of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, heated to 80°C and aged for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0071] The molar ratio of zinc ion and sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 6 is 1:20. The material responds to a NO2 concentration of 50 ppb under simulated sunlight irradiation, and responds after NO2 is introduced into the gas chamber for 13 seconds. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 86% of the initial state, and the stability is good.
[0072] Example 7
[0073] A method for preparing a gas-sensitive material with a molybdenite / ZnO heterogeneous pillared structure:
[0074] (1) 100 mg of molybdenite was dispersed in 100 mL of a 2.0 mol / L methanol solution of zinc acetate dihydrate, stirred at room temperature for 1 h to reach adsorption equilibrium, and 625 mL of an 8.0 mol / L methanol solution of sodium hydroxide was added, wherein the molar ratio of zinc ion to sodium hydroxide was 1:25. The mixture was stirred at 300 rpm for 2 h, centrifuged at 2000 rpm for 5 min, washed with deionized water 5 times and then washed with ethanol twice, and dried in vacuum at 25 °C for 24 h to obtain pillared molybdenite / ZnO nanoparticles.
[0075] (2) 100 mL of 2.0 mol / L zinc sulfate solution was dropped into 100 mL of 4.0 mol / L sodium hydroxide solution at 300 rpm, stirred for two hours, filtered and dried at 18°C for 24 hours.
[0076] (3) 100 mg of molybdenite / ZnO nanoparticles were dispersed in 10 mL of deionized water, added to 200 mL of 4.0 mol / L sodium hydroxide solution containing 3.48 g of ε-Zn(OH)2 and stirred at 300 rpm for ten minutes, aged at 60°C and 100°C for 0.5 h, then stirred at 300 rpm, washed and dried at 60°C overnight to obtain molybdenite / ZnO nanorods.
[0077] The molar ratio of zinc ions to sodium hydroxide in the pillared molybdenite / ZnO nanorod gas sensing nanomaterial synthesized in Example 7 is 1:25. The material responds to a NO2 concentration of 50 ppb under simulated sunlight irradiation, and responds 20s and 25s after NO2 is introduced into the gas chamber. When NO2 and other reactants are removed from the gas chamber, the resistance of the pillared molybdenite / ZnO nanorod pillared heterojunction material can return to 80% and 78% of the initial state, and the stability is good.
[0078] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing pillared molybdenite / ZnO nanorods, characterized in that: The following steps are involved: (1) under stirring, molybdenite is dispersed into zinc acetate methanol solution until adsorption equilibrium is obtained to obtain solution A for standby use; (2) adding sodium hydroxide methanol solution to solution A, continuously stirring, centrifuging, washing and drying to obtain molybdenite / ZnO nanoparticles; (3) dispersing the molybdenite / ZnO nanoparticles into deionized water and stirring evenly to obtain a molybdenite / ZnO nanoparticle suspension for later use; (4) Under stirring, the molybdenite / ZnO nanoparticle suspension is added to the sodium hydroxide solution of ε-Zn(OH)2, stirred for 10 minutes, aged at elevated temperature, stirred again, washed, and dried overnight to obtain the molybdenite / ZnO nanorods with heterogeneous pillared structure.
2. The method for preparing a pillared molybdenite / ZnO nanorod according to claim 1, characterized in that: The purity of MoS2 in the molybdenite is ≥99%.
3. The method for preparing a pillared molybdenite / ZnO nanorod according to claim 1, characterized in that: In step (1), the solid-to-liquid ratio of the molybdenite to the zinc acetate methanol solution is 1 mg: 1 mL; The concentration of the zinc acetate methanol solution is 2.0 mol / L.
4. The method for preparing a pillared molybdenite / ZnO nanorod according to claim 1, characterized in that: In step (2), the concentration of the sodium hydroxide methanol solution is 2.0-16.0 mol / L; In the step (2), the molar ratio of zinc ions to sodium ions is 1:6.25-25; The stirring speed is 0-600 rpm, the centrifugal speed is 2000 rpm, and the drying temperature is 20-30° C. for 12-24 hours.
5. The method for preparing a pillared molybdenite / ZnO nanorod according to claim 1, characterized in that: In step (3), the solid-liquid ratio of the molybdenite / ZnO nanoparticles to deionized water is 10 mg:1 mL; and the stirring speed is 0-600 rpm.
6. The method for preparing pillared molybdenite / ZnO nanorods according to claim 1, characterized in that: In step (4), the preparation method of the ε-Zn(OH)2 is: adding a sodium hydroxide solution dropwise into a zinc sulfate solution under stirring, reacting fully, washing and drying the precipitate to obtain ε-Zn(OH)2; The stirring speed is 0-600 rpm; the aging temperature is 60-100° C., and the aging time is 0.5 hour.
7. The method for preparing pillared molybdenite / ZnO nanorods according to claim 6, characterized in that: The concentration of the sodium hydroxide solution is 2.0-4.0 mol / L, the concentration of the zinc sulfate solution is 1.0-2.0 mol / L, and the molar ratio of the sodium hydroxide to the zinc sulfate is 2:1; The stirring speed is 100-700 rpm, and the drying is carried out at 15-20° C. for 22-26 hours.
8. The method for preparing pillared molybdenite / ZnO nanorods according to claim 1, characterized in that: In step (4), the mass ratio of ε-Zn(OH)2 to molybdenite / ZnO nanoparticles is 3.48:0.1, the liquid-to-solid ratio of the sodium hydroxide solution to molybdenite / ZnO nanoparticles is 200mL:0.1g, and the concentration of the sodium hydroxide solution is 4.0mol / L; The stirring speed is 200-800 rpm, and the stirring is repeated for 20-40 minutes. The drying condition is 60°C.
9. A method for preparing a pillared molybdenite / ZnO nanorod according to any one of claims 1 to 8, characterized in that: The purity of zinc acetate dihydrate used to prepare the zinc acetate methanol solution is ≥99%, and the purity of methanol is ≥99.5%; the purity of the sodium hydroxide is ≥99.5%, and the purity of the zinc sulfate is ≥99%.
10. An application of a pillared molybdenite / ZnO nanorod, characterized in that: The pillared molybdenite / ZnO nanorods obtained by the preparation method according to any one of claims 1 to 9 monitor ppb level NO2 at room temperature.
Citation Information
Patent Citations
Preparation method of ZnO / MoS2 nanosheet compound photocatalyst
CN106391059A
NO2 gas sensitive material solution and preparation method thereof
CN107727699A
NO2 gas sensor and its preparation method, use method and desorption method
CN107727700A
Sphalerite-based preparation of NO2 gas sensor with ZnS-ZnO heterojunction nanoparticles
CN109781796A
Manufacturing method of high-humidity-resistance gas sensor based on heterogeneous film
CN116698922A
